A New Model For Induction Motor With Induced Saliencies - Franco, Edison (2007)
This paper develops a formal and general model for an induction motor with periodic variations of the rotor slot; this induction motor with induced saliencies is commonly used in sensorless control applications. In order to obtain the model, first the analysis of the stator and rotor inductances modified by induced saliencies is carried out; second, the electromagnetic and electomechanical equations in ABC frame are developed and third, the model is represented in the natural orthogonal a-b frames. The obtained model is suitable for control design and compatible with the classical ab model for induction motors without saliencies.